Divided Spirits : Tequila, Mezcal, and the Politics of Production - Bowen, Sarah, 1978- (Book collections on Project MUSE., 2015)
Divided Spirits tells the stories of tequila and mezcal, two of Mexico's most iconic products. In doing so, the book illustrates how neoliberalism influences the production, branding, and regulation of local foods and drinks. It also challenges the strategy of relying on "alternative" markets to protect food cultures and rural livelihoods. In recent years, as consumers increasingly demand to connect with the people and places that produce their food, the concept of terroir--the taste of place--has become more and more prominent. Tequila and mezcal are both protected by denominations of origin (DOs), legal designations that aim to guarantee a product's authenticity based on its link to terroir. Advocates argue that the DOs expand market opportunities, protect cultural heritage, and ensure the reputation of Mexico's national spirits. Yet this book shows how the institutions that are supposed to guard "the legacy of all Mexicans" often fail those who are most in need of protection: the small producers, agave farmers, and other workers who have been making tequila and mezcal for generations. The consequences--for the quality and taste of tequila and mezcal, and for communities throughout Mexico--are stark. Divided Spirits suggests that we must move beyond market-based models if we want to safeguard local products and the people who make them. Instead, we need systems of production, consumption, and oversight that are more democratic, more inclusive, and more participatory. Lasting change is unlikely without the involvement of the state and a sustained commitment to addressing inequality and supporting rural development